Ontogenetic changes in diet and related morphological adaptations in Ocypode gaudichaudii. Issue 2 (2nd May 2016) - Lim, Shirley S.L.; Yong, Adeline Y.P.; Christy, John H.
Abstract: There are conflicting reports as to whether Ocypode gaudichaudii individuals switch from carnivory as juveniles to deposit‐feeding primarily on diatoms as adults, or whether they expand diet range and become omnivorous with maturity. At the onset of deposit‐feeding, crabs develop specialized claws with truncated ends that they use to shovel sediment during foraging. Eighty‐eight crabs were collected from Culebra Island (Republic of Panama) to study how the diet of this crab shifts with changes in claw shape, mouthpart proportions, and setation, as well as gastric mill width. Forty‐four crabs had identifiable material in their foreguts: 30 had animal material, 12 had diatoms, and two had a mix of both. There were no differences between the gastric mill, mandibles, and the proximal endites of the first maxillipeds of predators and deposit‐feeders, but extra rows of plumose setae were present on the second maxilliped of deposit‐feeding crabs with carapace length (CL) >10.6 mm. All individuals with CL <12.3 mm and non‐truncated claws ate animals, but those with larger CL and truncated claws had animal, diatom, or mixed diets; hence, claw truncation does not restrict the crab's diet to diatoms but, instead, broadens the diet to include both animals and diatoms. Perhaps this is a strategy to balance the economics of foraging on animals and diatoms on medium to low‐energy beaches that lack the larger invertebrates that adults of other species of ghost crabs eat. More generally, our study shows that specialized feeding structures need not imply a narrow or specialist diet.